Metabolic Insights into the Anion-Anion Antagonism in Sweet Basil: Effects of Different Nitrate/Chloride Ratios in the Nutrient Solution - Corrado, Giandomenico (Int J Mol Sci, 2020)
Sweet basil (Ocimum basilicum L.) is a highly versatile and globally popular culinary herb, and a rich source of aromatic and bioactive compounds. Particularly for leafy vegetables, nutrient management allows a more efficient and sustainable improvement of crop yield and quality. In this work, we investigated the effects of balanced modulation of the concentration of two antagonist anions (nitrate and chlorine) in basil. Specifically, we evaluated the changes in yield and leaf metabolic profiles in response to four different NO(3)(−):Cl(−) ratios in two consecutive harvests, using a full factorial design. Our work indicated that the variation of the nitrate-chloride ratio exerts a large effect on both metabolomic profile and yield in basil, which cannot be fully explained only by an anion-anion antagonist outcome. The metabolomic reprogramming involved different biochemical classes of compounds, with distinctive traits as a function of the different nutrient ratios. Such changes involved not only a response to nutrients availability, but also to redox imbalance and oxidative stress. A network of signaling compounds, including NO and phytohormones, underlined the modeling of metabolomic signatures. Our work highlighted the potential and the magnitude of the effect of nutrient solution management in basil and provided an advancement towards understanding the metabolic response to anion antagonism in plants.